Analysis of LINE 17 Work Using the 5S Method as an Effort to Prevent Work Accidents at PT. XYZ: Analisis Pada Pekerjaan LINE 17 Menggunakan Metode 5S Sebagai Upaya Pencegahan Kecelakaan Kerja di PT. XYZ - Daffa A. Hartono; Rizqi N. Sari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT XYZ is one of the leading companies in the food and beverage sector in Indonesia. PT XYZ faces challenges in its work environment in the form of irregular placement of goods. This problem can have a negative impact on the company and employees, especially in the field of occupational health and safety. This study aims to design steps that can minimize potential occupational hazards for employees using the 5S method (Seiri/Sort, Seiton/Straighten, Seiso/Shine, Seiketsu/Standardize, and Shitsuke/Sustain). The results of observation and analysis show that the implementation of the 5S method at PT XYZ has not been carried out optimally. Untidy and unclean conditions can cause discomfort for workers in carrying out their activities, and even have the potential to cause work accidents. The proposed improvements that can be considered by PT XYZ on Line 17 are sorted according to the points in the 5S method. From the results of the analysis of the proposed implementation of the 5S method, it is hoped that the company can make improvements as an effort to prevent work accidents.